Evolution of Periodic Orbits within the Frame of Formation Satellites - Elbaz I. Abouelmagd; Mitali J. Doshi; Niraj M. Pathak (Advances in Astronomy)
In the framework of formation satellites, the periodic orbits of deputy satellite are analyzed when the chief satellite is moving in an elliptical orbit. This analysis is developed on 1- to 10-loop periodic orbits of the deputy satellite. These orbits along with their associated loops are discussed under some specific initial position sets. The effects of different initial velocities, initial true anomalies, and eccentricities on the initial position and orbital period of periodic orbits of deputy satellite are investigated.